ETOS KERJA PEREMPUAN PADA SEKTOR KEBUN TANAMAN CENGKEH DI DESA PUULEMO KECAMATAN LEMBO KABUPATEN KONAWE UTARA - Sukmawati Abdullah; Hartina Batoa; Pratiwi Andriyani Mekuo (Agriplus, 2014)
This study aims to assess the women work level clove plant in working the garden in the Puulemo Village, Lembo District, North Konawe. The way to get  the research purpose was done by taking three variables: the identity of the respondents (age, education and experience of trying to farm), a work ethics (discipline, morale and mutual cooperation), and the value of culture (norms, social interaction and the principle of kinship). The population in this research women farmers who work in clove plantations 108 people , with a total sample is 27 respondents , or about 25 % by using Simple Random Sampling technique . The women farmers work ethics level can be assessed by using the formula interval . The results showed that women work level in working at garden clove plant are in the high category .   Keywords : women farmers, work ethics, clove plantations